2017
DOI: 10.1016/j.ijcard.2016.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Combining heart rate and systolic blood pressure to improve risk stratification in older patients with heart failure: Findings from the RICA Registry

Abstract: The combination provides better risk discrimination than use of HR and SBP alone and may provide a simple and reliable tool for risk assessment for older HF patients in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In summary, according to many authors the prognostic role of BP and HR in HF outcome cannot be overestimated. Some authors have suggested that combining HF and SBP constitutes a valuable prognostic factor in older patients with HF [39]. Nevertheless, there are still few reports concerning the prognostic value of HR and SBP combinations, products or quotients in patients with CHF.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, according to many authors the prognostic role of BP and HR in HF outcome cannot be overestimated. Some authors have suggested that combining HF and SBP constitutes a valuable prognostic factor in older patients with HF [39]. Nevertheless, there are still few reports concerning the prognostic value of HR and SBP combinations, products or quotients in patients with CHF.…”
Section: Discussionmentioning
confidence: 99%